Ответы и объяснения

  • Luska
  • середнячок
2012-09-20T19:14:37+00:00

-х2-24х+1=0

тут вообще че нужно делать?я упростила.

2х2+4х+1-3х2-12х-4=4х-6х-6х-9-13

2012-09-20T20:04:19+00:00

(2x+1)^2-(3x-2)^2=(2x-3)(2x+3)+13.

Используем формулу разница квадратов:

а² - б² = (а + б)(а - б)

2х + 1 = а,   3х - 2 = б  ⇒ (2х + 1 + 3х - 2)(2х + 1 -3х + 2) = 4х² - 9 + 13 

⇒(5х -1)(3 - х) = 4х² + 4

15х - 5х² - 3 + х = 4х² + 4 

16х - 5х² - 4х² = 4 + 3

-9х² + 16х - 7 =0 

9х² - 16х +7 =0

Ищим дискриминант:

Д = (-16)² - 4 * 9 * 7 = 256 - 252 = 4 = 2²

х1 = (16 - 2) / 2 * 9 = 7/9;    х2 = (16 + 2) / 2  * 9= 1

Ответ: х1 = 7/9  или х2 = 1